Ancient and recent (post-agricultural) forest communities as indicators of environmental conditions in north-eastern Poland (Masuria and Kurpie region) - Roo-Zielińska, Ewa (1948– ); Matuszkiewicz, Jan Marek (1946– ) (IGiPZ PAN, 2016)
The paper analyses three forest types belonging to the following associations: (1) fresh pine forest (Peucedano-Pinetum), (2) mixed pine forest (Querco roboris-Pinetum) and (3) oak-hornbeam forest (Tilio cordatae-Carpinetum betuli). They are located in north-eastern Poland. We compared the indicator value of three sets of data: (1) phytosociological relevés representing ancient forests (each type/association), (2) phytosociological relevés representing the youngest recent forests with the shortest regeneration period (each type/association) and (3) the ‘abstract pattern’ (representing the core of a specific type of plant community with a characteristic combination of species and clearly representing a separate type of ecosystem/association). Three sets of data together with their indicator values/numbers: light intensity (L), soil moisture (F), soil reaction (R), and nitrogen supply (N) according to the Ellenberg scale, constituted the basic material for comparative indicator analysis. The percentage shares of ecological groups of species have been calculated as well as the average indicator values for each of these within a data set. The results obtained show that the ‘abstract pattern’ can be treated as a good measure for the evaluation of ancient forest habitat conditions; it is clearly visible in the mean L and F indicator values of the Peucedano-Pinetum and Querco-Pinetum associations, and also in the N of Peucedano-Pinetum and R of Querco-Pinetum, which are closer to ancient forest than to recent forest. In all cases, we found ecological differences between the ancient and recent forests based on their indicator values. Statistically significant differences of the mean L indicator values between ancient forest and recent forest have been found in three types of forest community.
24 cm
Keywords: characteristic combination of species; Ellenberg ecological indicator values; ancient and recent forests